News from Nowhere. A Platform for the Future & Introspection of the Present : A project by Moon Kyungwon & Jeon Joonho. - Choe Jae Chun; Changdong, Lee; Dobrian, Christopher; Imamura, Yusaka; Jeonwang, Joe; Khoo, Eric; Mvdr; Obrist, Hans Ulrich; Tsumura, Kosuke; Un, Ko; Zanzotto, Andrea (Seoul : Workroom Press, 2012)
Ito, Toyo ; Iemura, Kayoko ; Joonho, Jeon
The end of the world, nature desasters, tsunami Fukushima 2011, new technologies for construction, new commons.
boek